Laboratory toxicity and large-scale commercial validation of the efficacy of ethanedinitrile, a potential alternative fumigant to methyl bromide, to disinfest New Zealand Pinus radiata export logs. (September 2020) - Najar-Rodriguez, Adriana J.; Afsar, Saeedeh; Esfandi, Kambiz; Hall, Matthew K.D.; Adlam, Anthony R.; Wilks, Catherine; Noakes, Emma; Richards, Kate
Abstract: We tested the efficacy of ethanedinitrile (EDN), a new fumigant considered as a potential methyl bromide (MB) replacement for the quarantine treatment of New Zealand pine, Pinus radiata D. Don, export logs. Firstly, toxicity trials were conducted in the laboratory with pine logs infested with the larvae, pupae, or adults of pine bark beetles, Hylurgus ligniperda and Hylastes ater, at 10 and 20 °C in 28-L chambers, to identify the most tolerant species and life stages. Then, logs infested with the most tolerant species and life stage were fumigated in 500-L laboratory chambers to determine whether the increase in the volume of the fumigated space and logs that will occur when scaling up from laboratory to commercial fumigations would affect EDN efficacy. Finally, confirmatory fumigation trials using commercial or semi-commercial sized log stacks, were conducted in a deforested commercial plantation area in Tokoroa, New Zealand, to demonstrate the efficacy of EDN in the field. Our results suggest EDN could be an effective alternative fumigant to MB for the phytosanitary treatment of logs exported from New Zealand . A phytosanitary fumigation schedule with EDN for P. radiata export logs that uses a concentration of 100 g/m 3 for 20 h across a range of temperatures from 10 to 20 °C is recommended. Future efforts should focus on implementing the recommended schedule, under commercial practices, to provide quarantine security for export logs using EDN as a replacement for MB. Graphical abstract: Image 1 Highlights: Postharvest quarantine treatments require alternatives to methyl bromide, an ozone-depleting fumigant. Ethanedinitrile was tested as an alternative to methyl bromide for the control of forest pests associated with export pine logs. Results confirmed ethanedinitrile as a promising phytosanitary alternative to methyl bromide for export pine logs.